Enrichment of motile spermatozoa from cattle semen samples by microfluidics method - Yata, Vinod Kumar; Yadav, Neeraj; Katoch, Vibhav; Gangwar, Dharmendra Kumar; Kumar, Sudarshan; Mohanty, Tushar Kumar; Prakash, Bhanu; Mohanty, Ashok Kumar (The Indian Journal of Animal Sciences, 2022)
Motile sperm cell separation is important in sample preparation for both artificial insemination and cryopreservation of semen. A novel microfluidic device consisting of an inlet microchannel, a separating reservoir and two outlet microchannels was developed to enrich the motile sperm cells of cattle semen samples. Sperm separation was performed in this microfluidic device using a continuous flow process based on the swim up behaviour of motile cells. Separating reservoir allows the high motile sperm cells to swim up and pass through the top outlet of the reservoir. Low and non-motile sperm cells pass through the bottom outlet of the reservoir in the direction of fluid flow. The microfluidic device was fabricated using polydimethylsiloxane (PDMS) and semen samples were infused into the microfluidic device through a syringe pump. Sperm motility was analyzed by Computer-assisted sperm analysis (CASA). More than 80% enrichment of motile spermatozoa in the cattle semen samples was observed after their separation in the fabricated microfluidic device.